Effects of hyperhydration on total body water, temperature regulation and performance of elite young soccer players in a warm climate - Rico-Sanz, J.; Frontera, W. R.; Rivera, M. A.; Rivera-Brown, A.; Mole, P. A.; Meredith, C. N. (International Journal of Sports Medicine, 1996)
The purpose of this study was to test the effect of increased fluid intake on temperature regulation and performance in elite soccer players. Eight players of the Puerto Rico National Team were studied under field conditions at a Wet Bulb Globe Temperature (WBGT) heat stress index of 25.3 +/- 0.5 degrees C. They were young (17.0 +/- 0.6 yr) and well aerobically conditioned, as shown by their maximum aerobic power of 69.2 +/- 0.7 ml.kg(-1).min(-1). Players were randomly allocated to a week of voluntary hydration (VH) (fluid intake = 2.7 +/- 0.2.day(-1)) and a week of hyperhydration (HH) (fluid intake = 4.6 +/- 0.2.day(-1)) (p <0.05) prior to a soccer match. Their total body water (TBW) increased in HH compared to VH (p<0.05), despite a significant increase in urine output (p < 0.01). The soccer match was played at 82 +/- 7% (VH) and 83 +/- 6% (HH) of maximum heart rate. Sweat losses and core temperature increases during the match were similar in both hydration conditions. When the environmental conditions were taken into consideration, the increase in core temperature during the match rose, as a function of the heat stress index, only in VH (p < 0.05). Plasma volume was slightly reduced in both hydration conditions (ns). Performance assessment at the end of the soccer match revealed that average time to complete 7 repetitions of a soccer specific test was significantly increased (p < 0.05) after the match in both hydration conditions but showed no difference between them. Peak torque and fatigability of knee flexor and extensor muscle groups at 240 deg.sec(-1), measured on a Cybex 340 dynamometer were similar in both hydration conditions and not affected by the soccer match. The data suggest that additional water intake in these heat-acclimated players increased body water reserves and improved temperature regulation during a soccer match with no significant effect on the decrement in soccer specific performance observed at the end of a soccer match.